Din al-Fitrah (Primordial Religion): Nurturing inter-religious dialogue and beyond in al-Faruqi’s thought - Shehu, Fatmir Mehdi (2013)
The thrust of this paper is to analyze Ismail Raji al-Faruqi’s thoughts on inter-religious dialogue activities between Muslims and others. It discusses al-Faruqi’s thought on DÊn al-FiÏrah (Primordial religion), as a spiritual basis to nurture inter-religious dialogue and beyond between Muslims and others in general and the People of the Book in particular, Jews and Christians. This study will focus on al-Faruqi’s brief bibliography and his thought towards inter-religious dialogue activities. A critical analysis will be done on al-Faruqi’s approach towards DÊn al-FiÏrah as a religious norm that nurtures inter-religious dialogue and beyond by composing the differences between religions. The findings of this study will enrich the perspective of modern comparative religious studies with the insights of the original efforts and contribution of contemporary Muslim scholar and thinker, Ismail Raji al-Faruqi, in inter-religious dialogue scholarship.